The effect of L-carnitine supplementation on lipid profile in adults: an umbrella meta-analysis on interventional meta-analyses - Musazadeh, Vali; Alinejad, Hanie; Esfahani, Niloofar Kouhi; Kavyani, Zeynab; Keramati, Majid; Roshanravan, Neda; Mosharkesh, Erfan; Dehghan, Parvin (Frontiers in Nutrition, 2023)
Introduction Previous meta-analyses investigating the therapeutic effects of L-carnitine on lipid profiles have demonstrated inconsistent results. The present umbrella meta-analysis aimed to investigate the impact of efficacy of L-carnitine on lipid profiles in adults. Methods Databases including PubMed, Scopus, and Embase, Web of Science, and Google Scholar were searched up to June 2023. Meta-analysis was performed using a random-effects model. Results Our results from thirteen meta-analyses indicated that L-carnitine supplementation significantly total cholesterol (TC) (ES = −1.05 mg/dL, 95% CI: −1.71, −0.39; p = 0.002), triglycerides (TG) (ES = −2.51 mg/dL; 95% CI: −3.62, −1.39, p < 0.001), and low-density lipoprotein-cholesterol (LDL-C) (ES = −4.81 mg/dL; 95% CI: −6.04, −3.59; p < 0.001). It also increased high-density lipoprotein-cholesterol (HDL-C) (ES: 0.66 mg/dL, 95% CI: 0.20, 1.12, p = 0.005) levels. Conclusion The present umbrella meta-analysis suggests supplementation with L-carnitine in a dosage of more than 2 g/day can improve lipid profile. Thus, L-carnitine supplementation can be recommended as an adjuvant anti-hyperlipidemic agent.